Dynamics of leaf, flower and fruit abscission in avocado cv. Hass in Antioquia, Colombia - Bernal-Estrada, Jorge Alonso; Tamayo-Vélez, Alvaro de Jesús; Díaz-Diez, Cipriano Arturo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The amount of leaf litter produced by avocado trees cv. Hass is an important potential source of mineral resources, and quantifying its production and nature is crucial to understanding the cycling of nutrients. The main objective of this study was to quantify the production of leaf litter and fallen flowers and small fruits in avocado orchards at eight locations in three producing areas in the Department of Antioquia (west, southwest, and north). The highest leaf litter production occurred in southwest Antioquia, at Jardin (7.6 t ha-1 year-1); the east locations had similar leaf fall (4.03-3.4 t ha-1 year-1). The dry matter produced in the north was very similar in both locations. The dry matter was 2.8 t ha-1 year-1. Higher leaf litter was recorded in all locations during the driest periods. Approximately 80% of the fallen fruits had diameters less than 1 cm. The highest flower production and fall occurred in southwest Antioquia, followed by the northern region.